# equation is not equivalent to the others

Which equation is not equivalent to the others?

zero point four x equals one point two

six x equals eighteen

two x equals zero point six

x equals three

### Comments for equation is not equivalent to the others

 Mar 24, 2014 not equivalent by: Staff Answer Part I Which equation is not equivalent to the others? zero point four x equals one point two six x equals eighteen two x equals zero point six x equals three The first thing to do is to translate the words into mathematical symbols. 1st equation: English Language Version zero point four x equals one point two the translation to mathematical symbols: "zero" can be replaced with the number: 0 "point" can be replaced with a decimal point: . "four" can be replaced with the number: 4 x is the unknown. Just leave it as x. "equals" can be replaced with the equal sign: = "one" can be replaced with the number: 1 "point" can be replaced with a decimal point: . "two" can be replaced with the number: 2 the final equation, using mathematical symbols instead of words: 0.4x = 1.2 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part II 2nd equation: English Language Version six x equals eighteen the translation to mathematical symbols: "six" can be replaced with the number: 6 x is the unknown. Just leave it as x. "equals" can be replaced with the equal sign: = "eighteen" can be replaced with the number: 18 the final equation, using mathematical symbols instead of words: 6x = 18 3rd equation: English Language Version two x equals zero point six the translation to mathematical symbols: "two" can be replaced with the number: 2 x is the unknown. Just leave it as x. "equals" can be replaced with the equal sign: = "zero" can be replaced with the number: 0 "point" can be replaced with a decimal point: . "six" can be replaced with the number: 6 the final equation, using mathematical symbols instead of words: 2x = 0.6 4th equation: English Language Version x equals three the translation to mathematical symbols: x is the unknown. Just leave it as x. "equals" can be replaced with the equal sign: = "three" can be replaced with the number: 3 the final equation, using mathematical symbols instead of words: x = 3 the four equations, expressed in mathematical symbols, are: zero point four x equals one point two: 0.4x = 1.2 six x equals eighteen: 6x = 18 two x equals zero point six: 2x = 0.6 x equals three: x = 3 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part III What does the term "equivalent" actually mean? There is a difference between equivalent values, equivalent expressions, and equivalent equations. Here are some examples: Equivalent values: The value of 500 pennies is equivalent to the value of a \$5 bill. Both have the same purchasing power. You can purchase an item costing five dollars with a \$5 bill, or with 500 pennies. A distance of 5 ½ feet is equivalent to 66 inches. 1 hour is equivalent to 60 minutes, or 3600 seconds. Equivalent expressions: Equivalent expressions are not equations. 3(x^2 + 1) and 3x^2 + 3 are equivalent expressions regardless of what the value of x turns out to be. Equivalent equations: (x + 5)^3 = 0 and x = -5 are equivalent equations. (However, (x + 5)^3 and x are definitely not equivalent expressions for all values of x.) Equivalent equations will always have the same solution. The easiest way to find out which equation is not equivalent to the others is to solve for the value of x in all four equations. When the value of x in three of the equations is the same, and the value of x in the "other equation" is a different value, the "other equation" is the answer. ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part IV Solve for x in each equation: 1st equation: zero point four x equals one point two: 0.4x = 1.2 solve for x by dividing each side of the equation by 0.4 0.4x = 1.2 (0.4x = 1.2) / 0.4 0.4x / 0.4 = 1.2 / 0.4 (0.4 / 0.4) * x = (3 * 0.4) / 0.4 (0.4 / 0.4) * x = 3 * (0.4 / 0.4) (1) * x = 3 * (1) x = 3 for the equation 0.4x = 1.2 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part V 2nd equation: six x equals eighteen: 6x = 18 solve for x by dividing each side of the equation by 6 6x = 18 (6x = 18) / 6 6x / 6 = 18 / 6 (6 / 6) * x = (3 * 6) / 6 (6 / 6) * x = 3 * (6 / 6) (1) * x = 3 * (1) x = 3 for the equation 6x = 18 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part VI 4th equation: x equals three x = 3 for the equation x = 3 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part VII 3rd equation: two x equals zero point six: 2x = 0.6 solve for x by dividing each side of the equation by 2 2x = 0.6 (2x = 0.6) / 2 2x / 2 = 0.6 / 2 (2 / 2) * x = (0.3 * 2) / 2 (2 / 2) * x = 0.3 * (2 / 2) (1) * x = 0.3 * (1) x = 0.3 for the equation 2x = 0.6 ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part VIII Final Answer: 2x = 0.6 is not equivalent to the other equations It is also worth noting that the three equivalent equations (0.4x = 1.2, 6x = 18, and x = 3) are also dependent equations. Each of the three equations can be derived from either of the other two equations. ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part IX The second equation (6x = 18) can be derived by multiplying the first equation (0.4x = 1.2) by 15. 0.4x = 1.2, first equation 15 * (0.4x = 1.2) 15 * 0.4x = 15 * 1.2 6x = 18, second equation Likewise, the first equation (0.4x = 1.2) can be derived by dividing the second equation (6x = 18) by 15. 6x = 18, second equation (6x = 18) / 15 6x /15 = 18 / 15 (2 * 3)x / (5 * 3) = (3 * 6) / (3 * 5) (2 / 5) * (3 / 3) * x = (3 / 3) * (6 / 5) (2 / 5) * (1) * x = (1) * (6 / 5) (2 / 5) * x = (6 / 5) (0.4) * x = (1.2) 0.4x = 1.2, first equation As already shown above, the equation (x = 3) can be derived by dividing the first equation (0.4x = 1.2) by 0.4. It can also can also be derived by dividing the second equation (6x = 18) by 6. ------------------------------------------------------

 Mar 24, 2014 not equivalent by: Staff ------------------------------------------------------ Part X The other equation (2x = 0.6) cannot be derived from any of the other equations. Again, the answer to your question is: 2x = 0.6 is not equivalent to the other equations Thanks for writing. Staff www.solving-math-problems.com

 Dec 15, 2017 Math solve the class of element topic. Of binomial theorm NEW by: Abhishek raj The general term of expansion

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.

Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com